Customer Expectation, Perceived Value and The Moderating Influence of Islamic Attributes of Destination On Customer Satisfaction in Jordan - Mustafa Hassan Abdullah Alshamaileh
Globally, various types of tourism have increased over the decades with Islamic tourism being an increasing industry in its own sphere. National and international Muslim travellers' communities have a predetermined awareness of Islamic attributes regarding what to expect at hotels, restaurants, beaches and religious or non-religious locations while they are visiting Jordan. The research sought to ascertain which Islamic attributes are hndanlental to Muslim tourists while they were visiting Jordan and the impacts they have on promoting Jordan as an Islamic destination and, in the future, becoming an integral part of Islamic tourism. A self-administered questionnaire was used to collect data from national and international Muslim tourists in various regions of Jordan in order to examine how Islamic attributes affect the choice of their destinations. Data was collected utilising internationally accepted measurement tools Structural Equational Modelling. 370 questionnaires were entered and analysed by AMOS 20; the variance being 0.32 for overall tourists' satisfaction. The findings indicate that Islamic attributes on destinations have a significant impact as a moderating influence on tourists' satisfaction levels and diversify according to the attributes and have divergent levels of satisfaction. Finally, the study concludes that there should be increased collaboration between Jordan and other nations but at the same time not overlooking its domestic market to attract Muslim tourists at competitive prices, the enhancement of the quality of tourism services to the highest international standards and upgrading facilities in Jordan specifically in prominent tourist catchment areas especially for Muslim tourists.